Gamified experience design: a case study on China's immersive tourist blocks in historic cities - Zheng, Yuqi; Zhang, Jiayi; Li, Jinsha (Frontiers in Sustainable Tourism, 2024)
IntroductionIn the context of the internet economy era, historic cities face increasing pressure to attract tourists through effective urban design strategies. Immersive districts, particularly in historic Chinese cities, have emerged as an innovative approach to enhance tourism experiences, achieving notable success. This paper explores the use of immersive design strategies in the Guitanglou (簋唐楼) district in Xi'an, China, with a focus on gamification theory.MethodsThe study employs in-depth interviews and content analysis to examine the design strategies employed in the Guitanglou immersive district. Through these methods, the research investigates how immersive experiences can be used to enhance tourist engagement in historic sites.ResultsThe research introduces a “4S” design model, consisting of Scene, Socialization, Story, and Stimulus. The model suggests that by innovating design within these four key areas, tourists can engage more deeply with the immersive district, resulting in stronger cultural resonance and emotional connections.DiscussionThis study offers new insights into tourism and urban design, highlighting how immersive districts can serve as effective platforms for disseminating historical and cultural values. The findings suggest that leveraging communication strategies familiar to digital natives can create a balance between cultural preservation and economic growth, offering a fresh perspective on urban design in historic settings.